Heritability estimates for 361 blood metabolites across 40 genome-wide association studies - Fiona A. Hagenbeek (Nature Portfolio, 2020)
Blood metabolite levels are under the influence of environmental and genetic factors. Here, Hagenbeek et al. perform heritability estimations for metabolite measures and determine the contribution of known metabolite loci to metabolite levels using data from 40 genome-wide association studies.